COMMUNITY EMPOWERMENT THROUGH HEALTH EDUCATION ON HEPATITIS B TRANSMISSION IN PREGNANT MOTHERS AND NEWBORN BABIES - Elsidianastika Trisnawati, Reineldis; S. Banul, Maria; T. Dalmini, Priska (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Pregnant women with a positive HBsAg risk are very dangerous to the fetus in the mother's womb because it can threaten the safety of the mother and her baby. This assistance to babies is a key step in creating a new generation that is free of Hepatitis B. At the Wae Mbeleng Health Center, the number of cases of pregnant women with hepatitis B in 2020 was 40 cases, compared to the 2019 data, which was 35 cases. The high cases of hepatitis B infection in pregnant women at the Wae Mbeleng Public Health Center is a big concern for the public to be more aware of the dangers of this infection, both for mothers and their children. Therefore, the community needs to be given education about HBV, to break the chain of transmission of this infectious disease. The purpose of this activity is to increase public knowledge about the hepatitis B virus and increase awareness for screening. This service activity was carried out for 3 months. The participants of this activity were 30 pregnant women. The method of implementing the activity is through counseling, as a promotive and preventive effort in controlling hepatitis B virus infection. The results of this activity are an increase in public knowledge seen from the posttest. The ability of participants in mastering the material after the counseling activity can be said to be good (83.3%).